US Espionage against Poland in 1970–1989 - Rosicki, Remigiusz (WNPiD UAM, 2019)
The objective scope of the research problem presented in the text covers a selection of issues concerned with the US espionage against Poland in the period between 1970 and 1989. The main goal of the text is to present the Polish intelligence services' state of knowledge and habits of mind concerned with the threats springing from the US spying activity. In order to elaborate the research problem, the following research questions have been presented: (1) What was the scope of the recognition of the US espionage by the Polish intelligence services in the period of 1970-1989?, (2) What areas of interest in the US espionage against Poland were predominant in the period of 1970-1989? The text focuses on: (1) an overall description of espionage in Poland (allowing for both the quantitative aspects of the phenomenon and the legal aspects), (2) areas of interest for the US intelligence in Poland (taking into account both the activity of US diplomatic posts and some selected spheres of interest to the US intelligence services, e.g. economy, industry and academia). The text uses material and documentation generated by the Ministry of the Interior and the Ministry of Defence (including subordinate institutions, e.g. special services) in the years 1970-1989. The theory of speech acts by J. L. Austin has been liberally used to critically analyse the material and documentation. Besides, a dogmatic interpretation of the law has been used to analyse the legal issues of espionage.
Keywords: espionage; szpiegostwo; spying activity; działalność szpiegowska; intelligence activity; działalność wywiadowcza; counter-intelligence activity; działalność kontrwywiadowcza; US espionage; szpiegostwo USA; intelligence services; służby specjalne; state security; bezpieczeństwo państwa; information security; bezpieczeństwo informacji